Pengaruh Pupuk Organik Terhadap Pertumbuhan Tanaman Cabai Merah (Capsicum annuum L.) (International Forum of Researchers and Lecturers, 2024)
The red chili plant (Capsicum annuum) is a horticultural plant that has high economic value. Red chilies can ward off free radicals, besides red chilies contain vitamin A. The need for red chilies continues to increase, but the availability of red chilies is still very low compared to the demand and needs of the community. Therefore, to increase the availability of chilies, the growth of red chili plants (Capsicum annuum) is an important subject in modern agriculture, with the use of organic fertilizer being a significant research focus in an effort to increase productivity and plant health. This research aims to evaluate the effect of organic fertilizer on the growth of red chili plants.